Factors Affecting Students’ Behaviour in Cultural Creative Arts and History Subject in Junior Secondary Schools in Owerri North L.G.A., Imo State - Alaribe, C. O.; Onyebuchi, G. C.; Okoye, A. O.; Alison, J. O.; Nwaigwe, O. (Journal of Research in Adult and Continuing Education, 2024)
The focus of this study was to examine factors that affect students’ behavior in Cultural and Creative Arts and History Subject in junior secondary schools in Owerri North L.G.A. of Imo State. Four research questions guided the study. Descriptive survey research design was used for the study. The population consisted of 2,300 JSS 2 students of government owned schools in Imo State. A total of 260 JSS 2 students were randomly selected to constitute the sample.The instrument for data collection was titled Questionnaire on Students’ Behavior in Cultural and Creative Arts and History (QSBCCAH). The instruments were validated by three experts from Departments of Fine Arts, Psychology/Guidance and Counseling and Measurement & Evaluation Unit in Alvan Ikoku Federal University of Education Owerri, Imo State. The instrument was trial-tested on a sample of 20 students of Methodist High School Owerri in Owerri Municipal LGA which is outside the study area. The responses were subjected to Cronbach Alpha Method which yielded reliability indices of 0.88. Mean and Standard Deviation were used to answer the research questions. The findings of the study showed that teachers have a significant impact on the students, and the use of instructional materials captures and shapes the students behavior in CCA and History Subjects. Findings of the study also revealed that an instructional method captures the interest of the students’ while unavailability of resources for teaching and learning affects students’ behavior in CCA and History Subject. The study recommended among others that teachers should develop a cordial relationship with students and source for more captivating instructional materials to teach CCA and History subject.